2018
DOI: 10.1007/s00464-018-6219-8
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue fluorescence of the ureter during colorectal surgery

Abstract: BackgroundIatrogenic ureteric injury is a serious complication of colorectal surgery. Incidence is estimated to be between 0.3 and 1.5%. Of all ureteric injuries, 9% occur during colorectal procedures. Ureteric stents are utilised as a method to reduce the risk of injury; however, these are not without risk and do not guarantee prevention of injury. Fluorescence is a safe and effective alternative for intraoperative ureteric localisation. This proof of principle study aims to assess the use of methylene blue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…Four good quality human studies and one animal study were identified (Table 2 , Supp. Table 3 and 4) [ 17 21 ]. Matsui et al reported visualization of the ureters in pigs after intravenous (IV) injection of methylene blue (MB), prompting clinical translation by others [ 18 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four good quality human studies and one animal study were identified (Table 2 , Supp. Table 3 and 4) [ 17 21 ]. Matsui et al reported visualization of the ureters in pigs after intravenous (IV) injection of methylene blue (MB), prompting clinical translation by others [ 18 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 and 4) [ 17 21 ]. Matsui et al reported visualization of the ureters in pigs after intravenous (IV) injection of methylene blue (MB), prompting clinical translation by others [ 18 21 ]. In humans, feasibility and dose-finding studies described MB use in open and laparoscopic abdominal procedures [ 18 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early results suggest a promising future for both techniques. Using the fluorescence of methylene blue excreted in urine after intravenous injection, Barnes et al [32] were able to identify 14 out of 64 ureters that were not visible in standard white light, and in 10 cases the technique showed the ureter to be in an unexpected location. However, these techniques are costly and technically difficult to develop for research teams and industrial partners.…”
Section: Discussionmentioning
confidence: 99%